Problem Etis Proyek Food Estate di Indonesia Ditinjau dari Etika Immanuel Kant - FIRENZE TONTA, REX (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2024)
This article focuses on ethical issues arising from food estate projects in Indonesia. When government political policies often carry the ethical view of utilitarianism, which argues that an action is said to be a good action if it brings benefits and happiness to as many peoples as possible. However, this view has a fatal weakness, namely that it does not guarantee justice or guarantee human rights. This is what will be explained in this article using Immanuel Kant’s ethics. The method used in this article is qualitative with a literature study approach. This article reveals findings that apply Kant’s ethics where a person cannot be sacrificed for any reason. In the context of food estate project, it cannot be at the expense of other people, whether for the food security of many people or the profits of a few political elites. Because every person who is valueable in himself, can never be used only as a tool or means. Rather, as an end in itself. This is in accordance with the second principle of the imperative category.